Penampilan hama pelipat daun Cnaphalocrosis medinalis imigran dan parasitoid elasmus sp. di pertanaman padi - Baehaki Suherlan Effendi (Jurnal Entomologi Indonesia, 2005)
Cnaphalocrosis medinalis (Guenee) is a potential rice pest. The research was conducted at Subang district, used randomized block design. The big plot with 80 m x 100 m is planed by Ciherang rice variety. The big plot is divided to two plots with each size 40 m x 100 m. The first plot controlled by fipronil insecticides, but another one do not controlled us untreated plots. The untreated plot is divided to 160 small plots with size 5 m x 5 m. Observation on 30 hills per plot of randomize three plots every weeks. The result of this research show that abundance of larvae and pupae of leap folder on Ciherang variety was bimodel with two peaks. These curve indicated that leaf folder development reach two generation in one season. The relationship curve between rice plant old and leaf damage was linear curve with correlated value was 87%, but relationship curve with correlated value was 95%. The leaf folder more develop on the vegetative phase than on generative phase. The existent of larvae parasitoid, Elasmus sp is very late and abundance began of 70 days rice old with 14.8 % larvae parasitism. In the nearest harvest the larvae parasitism up to 94.4%. Amount of  parasitoid is very high to reach 225 parasitoid per larvae on 70 days rice old. Analog rice growth on dry season 2002 a leaf damage level was 5-50% and effect to yield losses was 833.3 kg/ha grain dry harvested or loosing income was Rp. 1,085,550.